Construction of Mahadevtar Tunnel and Challenges Faced During its Stabilization - Adhikari, Pramod Krishna; Adhikari, Pragati; Bo, Zhang; Ping, Chen (KTFT Journal, 2024)
The Madadevtar tunnel, constructed by China State Construction Engineering Corp. Ltd. as the main contractor for Package 1, is situated in a lithology comprising rock from the Upper Nawakot and Bhimphedi Group. These rock successions are separated by the Mahabharat Thrust. The excavation method employed is the New Austrian Tunnelling Method (NATM), resulting in two fully lined tubes. During design and construction, variations in rock composition were encountered. Similarly, the expected support types for detailed design and construction also exhibited some diversity. Challenges during construction included weathered and jointed rock masses, fault and shear zones, and groundwater inflow. Overbreak and collapses occurred due to weak rock and joint conditions. Addressing these issues involved installing additional ribs, rock bolts, grouting, and replacing sections in some parts of left and right tunnels.